Long-term exposure to air pollution and lung function among children in China: Association and effect modification - Teng, Jingjing; Li, Jie; Yang, Tongjin; Cui, Jie; Xia, Xin; Chen, Guoping; Zheng, Siyu; Bao, Junhui; Wang, Ting; Shen, Meili; Zhang, Xiao; Meng, Can; et al. (Frontiers in Public Health, 2022)
Background: Children are vulnerable to the respiratory effects of air pollution, and their lung function has been associated with long-term exposure to low air pollution level in developed countries. However, the impact of contemporary air pollution level in developing countries as a result of recent efforts to improve air quality on children’s lung function is less understood. Methods: We obtained a cross-sectional sample of 617 schoolchildren living in 3 differently polluted areas in Anhui province, China. Two-year average concentrations of air pollutants at the year of spirometry and the previous year (2017-2018) obtained from district-level air monitoring stations were used to characterize long-term exposure. Forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and forced expiratory flow between 25% and 75% of FVC (FEF25-75) were determined under strict quality control. Multivariable regression was employed to evaluate the associations between air pollution level and lung function parameters, overall and by demographic characteristics, lifestyle, and vitamin D that was determined by liquid chromatography tandem mass spectrometry. Results: Mean concentration of fine particulate matter was 44.7 μg/m3, which is slightly above the interim target 1 standard of the World Health Organization. After adjusting for confounders, FVC, FEV1, and FEF25-75 showed inverse trends with increasing air pollution levels, with children in high exposure group exhibiting 87.9 [95% confidence interval (CI): 9.5, 166.4] mL decrement in FEV1 and 195.3 (95% CI: 30.5, 360.1) mL/s decrement in FEF25-75 compared with those in low exposure group. Additionally, the above negative associations were more pronounced among those who were younger, girls, not exposed to secondhand smoke, non-overweight, physically inactive, or vitamin D deficient. Conclusions: Our study suggests that long-term exposure to relatively high air pollution was associated with impaired lung function in children. More stringent pollution control measures and intervention strategies accounting for effect modification are needed for vulnerable populations in China and other developing countries.